EFEKTIVITAS PELAKSANAAN PROGRAM M-PASPOR DALAM PELAYANAN PENGURUSAN PASPOR KEPADA MASYARAKAT DI KANTOR IMIGRASI KELAS I KHUSUS TPI MEDAN - Oktavianti, Veronica; Hutahaean, Marlan; Tobing, Artha Lumban (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
This study aims to determine how effective the M-Paspor service is in passport management and to find out what are the differences between the M-Paspor service and the previous service model. The method used in this research is descriptive qualitative method. Data collection techniques with primary data collection in the form of observation and interviews, and secondary data collection in the form of documentation. The results of the research conducted concluded that according to the analysis of the indicators of effectiveness namely, understanding of the program, on target, on time, achievement of goals and differences in services in the M-Passport program with the previous model had a positive impact through indicators of real change having been achieved, but in understanding the program it is hoped that implementers can be more informative in providing information about passport services on the M-Paspor application. The policy recommendations are expected to increase socialization, display creativity in socialization, and the public can understand and understand the process of making passports properly and correctly.